Keanekaragaman Hayati pada Kawasan Hutan Konservasi dan Kegiatan Pengelolaan Hutan Berdasarkan Undang-Undang Nomor 41 Tahun 1999 Tentang Kehutanan - Merdian Tenti; M. Maulana Rifki; Nabila Syah Dita; Nurjanah Nurjanah; Pipi Krisnawati; Rezki Yeldiansyah; Sohibatul Jannah; Tsani Muhammad Syach; Ika Dwimaya Roza (CV. ALIM'SPUBLISHING, 2026)
Conservation forest are areas that have a strategic function in maintaining biodiversity, maintaining ecosystem balance, and ensuring the sustainability of natural resources. Indonesia, as one of the megabiodiversity countries, has a very high wealth of flora and fauna, thus requirung a sustainable forest management system supported by strong policies. This study aims to analyze the concept of biodiversity in conservation forest areas, the history of forest use, agreements in forest management, the scope of forest management, anf Forest Areas with Special Purposes (KHDTK) based on law Number 41 of 1999 concerning Forestry. The study used a qualitative method with a literature study approach (library research) through the review of various books, scientific journals, laws and regulation, and official documents related to forestry. Data were analyzed using a qualitative descriptive method by identifying, grouping, and interpreting relevant theories, concepts, and regulations. The result of the study indicate that sustainable forest management must integrate aspects of conservation, utilization, protection, and rehabilitation of forests in a balanced manner. Law Numer 41 of 1999 provides the legal basis for forestry management, which includes forestry planning, forest management, research and development, education and training, outreach, and forestry supervision. Furthermore, the establishment of KHDTK plays a crucial role in supporting research, education, training, and the preservation of cultural and religious values without altering the primary function of forest areas. Therefore, conservation forest management, supported by regulations, law enforcement, and synergy between the governmnet, communities, academics, and other stakeholders, is expected to maintain the sustainability of biodiversity while providing sustainable ecological, social, and economic benefits for current and future generations.